EVALUASI KEBIJAKAN PEMBERDAYAAN UMKM PADA UMKM OTAK-OTAK DI KAMPUNG SUNGAI ENAM LAUT KABUPATEN BINTAN - Andhini Syahrani; Wahjoe Pangestoeti; Reza Gemilang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Otak-otak MSMEs are a leading culinary icon of Bintan Regency based on local fishery potential in Kampung Sungai Enam Laut. Their development is constrained by limited capital, low digital literacy, and uneven sales distribution, necessitating a targeted policy evaluation. This study evaluates MSME empowerment policies by the Regional Government and analyzes supporting and inhibiting factors. Using a descriptive qualitative approach in Sungai Enam Laut Village, data were collected through in-depth interviews, observation, and documentation from DKUPP, Village officials, MSME actors, and the community. Data analysis utilized Miles and Huberman's interactive model with NVivo 15, applying Dunn's Policy Evaluation Theory (effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness) and Van Meter and Van Horn's Implementation Theory. The results show that the empowerment policy has been quite effective. Assistance, training, and mentoring positively impacted business capacity. Process efficiency is relatively easy, though bureaucratic procedures still consume time. Adequacy is helpful but has not met needs for capital and specialized equipment. Equity is good, government responsiveness is high, and targeting aligns with local business characteristics. The main supporting factors are coordination, communication, and commitment, while the main obstacles are lengthy procedures and limited resources.